EFEKTIVITAS PEMBELAJARAN FULLY DARING TERHADAP KEMAMPUAN PENALARAN MATEMATIS SISWA - Hr, Bq. Malikah; Pratama, Indah Arry; Munawarah, Pyo Apriliana (Media Pendidikan Matematika, 2020)
The purpose of this research were to describe: 1) the effect of fully online learning to the mathematical reasoning abilities of students; 2) the response of the students to the application of fully online learning. The research was a mixed-method using quantitative and qualitative methods with one group pretest-posttest design. There were 32 students of class XI MIA MA NW Wanasaba, Wanasaba Sub-District, East Lombok Regency as the sample. Instrument of this research was the mathematical reasoning abilities essay test consists of 10 questions on learning materials of limit function, observation and interviews. The quantitative data analysis using descriptive statistics with paired sampel t-test. The results of this research showed that: 1) according to the results of data analysis, it was discovered the value of Sig. (2-tailed) was 0.000 < 0.05, it means that H0 was rejected and Ha was accepted, this indicated that there was a difference between the pretest and posttest average. Based on the descriptive statistics, the average of pretest score was 71.03 higher than the posttest score was 59.97. It can be concluded that the fully online learning was no more effective to the mathematical reasoning abilities of students. 2) there were 16% of the students gave a positive response to the application of fully online learning, 84% of the others prefer the blended learning and students gave a less positive response to the application of fully online learning and it was considered less helpful in practicing the mathematical reasoning abilities of students.